Ambivalence on the Front Lines: Perceptions of Contractors in Iraq and Afghanistan. (January 2013) - Kelty, Ryan; Bierman, Alex
In the past several decades, the US military has increasingly relied on civilian contractors to provide a variety of core functions. Lagging behind this increased reliance on contractors is an understanding of how the presence of contractors influences civilian and military personnel. This research addresses this question using a unique study of US Department of Army civilians and military personnel serving in Iraq and Afghanistan. We find a substantial degree of ambivalence among both groups regarding the impact of contractors on the military and comparisons with contractors, but we also find a noticeable trend of comparative discontent beneath this apparent ambivalence. Results are discussed in the context of using ambivalence as a starting point for building a theoretical approach to more systematically understanding the role and effects of contractor integration in the military.